Analysis of The Implementation of Character Education at Madrasah Tsanawiyah Muhammadiyah Gedongtengen Yogyakarta - Permadi, Bagus Damar Galih; Achadi, Muh. Wasith (Journal of Educational Sciences, 2025)
This study aims to analyze the management of the implementation of character education at MTs Muhammadiyah Gedongtengen Yogyakarta. This program is motivated by institutional anxiety about the negative impact of social media, such as the rise of extreme thinking, and the need to fortify students' character in line with the vision of the madrasah. This study uses a qualitative approach with a case study design. Primary data were collected through semi-structured in-depth interviews with Madrasah Heads, Vice Heads, and PAI teachers, and validated through observation and documentation. The results of the study show that implementation runs as a holistic management cycle. Planning is participatory by involving cross-disciplinary teachers. The implementation of a unique service culture pressure, namely "caring, compassion, and diligence", is manifested through the example of teachers (e.g. congregational prayers) and proactive home visits. Evaluation is carried out consistently through monthly observation meetings and daily observations. This study concludes that this model works effectively. The most significant result was an increase in students' critical thinking skills in filtering information on social media, which fortified them from extreme understanding while strengthening their daily worship practices.